Can Airbnb’s Role as an Ecosystem Orchestrator Explain Its Reconfiguration of Ownership Advantages for Internationalisation? - Sabharwal, Gurveer (2019)
The Eclectic Paradigm of Foreign Production has been instrumental in explaining subsidiary activity by MNEs. While possession of tangible ownership advantages took precedence in Dunning's paradigm, Sharing Economy firms have achieved rapid internationalisation through their "asset-lite" business models. Airbnb's access to its hosts, platform and institutional forces, has reconfigured its ownership advantages. I explore Airbnb's role as a micro-meso-macro-level ecosystem orchestrator. By studying the firm's management of host relationships, networks and institutions, I study its ability to reconfigure ecosystem dynamics into ownership advantages.